Pengaruh Digital Marketing Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Cake House By Widya Gerai Oleh-Oleh Pekanbaru - Fachraini Marysa; Mandataris Mandataris (eCo-Buss, 2023)
The objective of this study was to ascertain the impact of word-of-mouth and internet marketing on Cake House customers' purchasing decisions. Pekanbaru souvenir shopping by Widya. The independent variables are digital marketing (X1) and word of mouth (X2), while the dependent variable is the purchase decision (Y). This study employs a descriptive and quantitative methodology. The participants included in this research were all customers of Cake House by Wizya Souvenir Shopping Pekanbaru. An incidental sampling strategy was used to choose 100 respondents for the sample. The data used in this study was gathered by the administration of questionnaires, which were then analyzed statistically using the SPSS software. Digital marketing influences purchase decisions, as does word of mouth; both digital marketing and word of mouth influence buy decisions at Cake House by Widya Souvenir Shopping Pekanbaru, according to the findings of this research.